Numerical Analysis of Bearing Capacity of a Ring Footing on Geogrid Reinforced Sand - Haidar Hosamo (Buildings, 2021)

(untitled)
A ring footing is found to be of practical importance in supporting symmetrical constructions for example silos, oil storage container etc. In the present paper, numerical analysis was carried out with explicit code FLAC3D 7.0 to investigate bearing capacity of a ring footing on geogrid reinforced sand. Effects of the ratio n of its inner/ outer diameter (Di / D) of a ring footing, an optimum depth to lay the geogrid layer were examined. It was found that an intersection zone was developed in soil under inner-side (aisle) of ring footing, contributing to its bearing capacity. Substantial increase of bearing capacities could be realized if ratio n of a ring footing was around 0.6. Numerical results also showed that, bearing capacity of a ring footing could increase significantly if a single-layer geogrid was laid at a proper depth under the footing. Similar contribution was found if a double-layer geogrid was implemented. However, such increases appeared to be rather limited if a triple-layer geogrid or a four-layer geogrid was used. A double-layer geogrid was recommended to increase the bearing capacity of a ring footing; the depth to lay this double-layer geogrid was also discussed.